Cerebellopontine angle meningioma extending into internal auditory canal presenting with unilateral facial weakness and sensorineural hearing loss: Case presentation with review of literature - Kumar, Ravinder; Jaiswal, Gagan; Bhargava, Abhishek; Kundu, Jyoti (Journal of Kathmandu Medical College, 2017)
Tumour types other than schwannomas are uncommonly encountered in the cerebellopontine angle, and unusual lesions extending into the internal auditory canal are even rarer. We herein present a case of a 50-year-old woman with a right cerebellopontine angle meningioma (measuring 34mm x 35mm x 36mm), arising from the posterior surface of the petrous bone or the petrotentorial junction, secondarily involving the internal auditory canal. Contrast enhanced MRI showed typical appearance of a meningioma, with calcifi ed fl at surface against the petrous bone, a hemispheric or ice-cream-cone shape sign, adjacent hyperostosis, and ‘dural tail’ extending from the tumour. Initial clinical evaluation revealed continued presence of a stable neurological defi cit such as unilateral headache, hearing loss, reduced taste sensation, positive corneal and conjunctival refl ex along with right facial weakness (House-Brackmann grade III) signalling towards the involvement of V, VII and VIII cranial nerve. The variation in the anatomy of the faciocochlear nerve bundle in relation to the tumour has to be kept in mind, and preservation of these vital neural structures should be the goal in every case. Tumour resection was performed through a suboccipital-retrosigmoidal approach with a good outcome. Ours is an unusual case report analysing the diagnostic and therapeutic issues, surgical management strategies and treatment outcomes related to this rare disease entity.Journal of Kathmandu Medical College Vol. 5, No. 1, Issue 15, Jan.-Mar., 2016, Page: 34-40